Developing Intrapersonal Intelligence Through Technique "Make-Believe Play" In Order To Make Characterized Early Age Children - Kurniah, Nina (Indonesian Journal of Early Childhood Education Studies, 2014)
This study aims to develop intrapersonal intelligence in realizing the characterized early childhood, through the technique of "make-believe play" in learning, meanwhile, the focus of the problem is how to optimize the intrapersonal intelligence in learning by using these techniques. This study is a class action research (classroom action research), followed by small experiments to see the effectiveness of actions taken. Subjects were 24 children aged 5-6 years old in group B, in the kindergarten Al-Muhajirin Bengkulu City. Selected activities in developing the character is the technique of "make-believe play" in the classroom. The research data obtained were processed using a percentage. The analysis showed that the application of "make-believe play" in learning, it can develop intrapersonal intelligence in an effort to make characterized early childhood.How to citeEliza, D. (2015). Reading Readiness of Kindergarten Students At-Taqwa Mosque East Jakarta.Ã‚Â Indonesian Journal Of Early Childhood Education Studies, 3(1), 1-6. doi:10.15294/ijeces.v3i1.9467